Etanercept/celecoxib on improving MRI inflammation of active ankylosing spondylitis: A multicenter, open-label, randomized clinical trial - Tu, Liudan; Zhao, Minjing; Wang, Xiaohong; Kong, Qingcong; Chen, Zena; Wei, Qiujing; Li, Qiuxia; Yu, Qinghong; Ye, Zhizhong; Cao, Shuangyan; Lin, Zhimin; Liao, Zetao; et al. (Frontiers in Immunology, 2022)
Objective: To investigate the efficacy and safety of clinical, magnetic resonance imaging (MRI) changes in active AS patients with etanercept and celecoxib alone/combined treatment. Methods: A randomized controlled trial was conducted in three medical centers in China. Adult AS patients with BASDAI ≥ 4 or ASDAS≥ 2·1, CRP＞6 mg/L or ESR 28 mm/1st hour were randomly assigned (1:1:1 ratio) to celecoxib 200mg bid or etanercept 50mg qw or combined therapy for 52 weeks. The primary outcomes were SPARCC change of sacroiliac joint (SIJ) and spine, proportion of patients achieving ASAS20 response at 52 weeks. Results: Between Sept 2014 and Jan 2016, we randomly assigned 150 patients (mean age, 32·4 years; mean disease duration, 109 months), 133 (88·6%) completed the study. SPARCC inflammation scores of SIJ and spine decreased in three groups and significant differences were found between combined group and celecoxib group (between group difference: -6·33, 95%CI (-10·56, -2·10) for SIJ; -9·53, 95%CI (-13·73, -5·33) for spine), between etanercept group and celecoxib group (between group difference: -5·02, 95%CI (-9·29, -0·76) for SIJ; -5·80, 95%CI (-10·04, -1·57) for spine). ASAS20 response rate were 44%, 58% and 84% in celecoxib, etanercept, combined group respectively and significant difference was only found between combined and celecoxib group. Conclusion: Etanercept with or without celecoxib decreases inflammation detected by MRI at one-year compared to celecoxib alone in active AS patients. The combination of etanercept and celecoxib was superior to celecoxib alone for the primary clinical response. Registration: ClinicalTrials.gov: NCT01934933.